Biological Control of Early Blight Disease on Tomato Plant on Al-Gabal Al-Akhdar District - Mohamed, Nwara A.; Saeed, Mohammed A.; El-Samman, M.G.; Abugharsa, Issa A. (Al-Mukhtar Journal of Sciences, 2001)
This study was conducted in Faculty of Agriculture Omar Al-Mukhtar University during the period 1999-2001 in which we tested the effects of microorganisms (Bacteria and fungi) that isolated from phylloplane of some Solanaceae and rhizosphere of some vegetable crop as biological agents to control Alternaria solani, 17 bacterial species belongs to (Flavobacterium, Micrococcus, Bacillus and Pseudomonas) and six Fungal genera belongs to (Penicillium, Alternaria, Aspergillus, Fusarium, Ulocladium and Stemphylium) were isolated from the phylloplane of some solanaceae, and 30 bacterial species from the genera (Bacillus and Pseudomonas) were isolated from the rhizosphere. The results of double antagonistic in the lab. Showed that Bacillus spp. Gave the highest antagonistic effect against A. solani followed by the Micrococcus and Pesudomonas species. On the other hand no inhibition zone were noticed when using fungal species except inhibition resulting from direct hyphal contact. The results of field studies indicated that the disease severity of early blight was also reduced when the leaves of tomato blants were inoculated with the causal agent of the disease and treated with Clavibacter sp. That isolated from phylloplane of pepper plants.